Soil warming increases soil temperature sensitivity in subtropical Forests of SW China - Yuan,Chaoxiang; Zhu,Guiqing; Yang,Shuangna; Xu,Gang; Li,Yingyun; Gong,Hede; Wu,Chuansheng (PeerJ, 2019)
Background Soil respiration (RS) plays an important role in the concentration of atmospheric CO2 and thus in global climate patterns. Due to the feedback between RS and climate, it is important to investigate RS responses to climate warming. Methods A soil warming experiment was conducted to explore RS responses and temperature sensitivity (Q10) to climate warming in subtropical forests in Southwestern China, and infrared radiators were used to simulate climate warming. Results Warming treatment increased the soil temperature and RS value by 1.4 °C and 7.3%, respectively, and decreased the soil water level by 4.2% (%/%). Both one- and two-factor regressions showed that warming increased the Q10 values by 89.1% and 67.4%, respectively. The effects of water on Q10show a parabolic relationship to the soil water sensitivity coefficient. Both RS and Q10 show no acclimation to climate warming, suggesting that global warming will accelerate soil carbon release.
Keywords: Global warming; Soil carbon efflux; Soil water sensitivity coefficient